Preparation of NiO/Ni Nanocomposites Under Microwave Irradiation and Its Catalysis for Reduction of 4-Nitrophenol - Li, Jiulong; Bae Ko, Weon (Asian Journal of Chemistry, 2014)
Nickel(II) hydroxide nanocomposites were synthesized by a reaction of nickel(II) acetate tetrahydrate [Ni(CH3COO)2·4H2O] and sodium hydroxide in ethanol under microwave irradiation for 5 min. The NiO/Ni nanocomposites were then prepared by calcining the Ni(OH)2 nanocomposites in an electric furnace at 700 °C for 2 h. The resulting heated products were examined by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. In addition, the reduction of 4-nitrophenol with sodium borohydride and the NiO/Ni nanocomposites as a catalyst was examined by UV-visible spectrophotometer.